# [ lớp 12]TÍCH PHÂN

R

#### recycle.bin96

$I1=\int_{ln3}^{ln5}(\dfrac{1}{e^{2x}+2.e^{-x}-3})dx$

$\mathrm{I1=\int_{ln3}^{ln5}(\dfrac{1}{e^{2x}+2.e^{-x}-3})dx = \int_{ln3}^{ln5} \left ( \dfrac{e^x}{e^{3x} - 3e^x + 2} \right )}$

Đặt $\mathrm{t = e^x}$ $\mathrm{\Leftrightarrow dt = d(e^x) \Leftrightarrow dt = tdx \Rightarrow dx = \dfrac{dt}{t}}$

Đổi cận:

\begin{align*}\mathrm{x = ln5 \rightarrow t = 5 }\\ \mathrm{x = ln3 \rightarrow t = 3}\end{align*}

$\mathrm{\Rightarrow \int_{3}^{5}\dfrac{dt}{(t-1)^2(t+2)} }$

Đến đây đơn giản rồi nhỉ

N

#### nguyenbahiep1

$I1=\int_{ln3}^{ln5}(\frac{1}{e^{2x}+2.e^{-x}-3})dx\\ I2=\int_{2}^{6}\frac{dx}{2x+1+\sqrt{4x+1}}$

[laTEX]I_1 = \int_{ln3}^{ln5}\frac{e^xdx}{e^{3x}-3e^x+2} \\ \\ e^x = t \\ \\ I_1 = \int_{3}^{5}\frac{dt}{t^3-3t+2} = \int_{3}^{5}\frac{dt}{(t-1)^2.(t+2)} \\ \\ I_1 = \int_{3}^{5}\frac{1}{9}(\frac{1}{x+2} -\frac{1}{x-1}+ \frac{3}{(x+1)^2} )dt[/laTEX]

đến đây là đơn giản rồi

[laTEX]\sqrt{4x+1} = t \Rightarrow x = \frac{t^2-1}{4} \\ \\ I_2 = \int_{3}^{5}\frac{\frac{tdt}{2}}{\frac{t^2-1}{2} + 1 + t } \\ \\ I_2 = \int_{3}^{5}\frac{tdt}{(t+1)^2 } = \int_{3}^{5}\frac{dt}{t+1} - \int_{3}^{5}\frac{dt}{(t+1)^2}[/laTEX]

R

#### recycle.bin96

$\int_{2}^{6}\dfrac{dx}{2x+1+\sqrt{4x+1}}$

Đặt:

$\mathrm{t = \sqrt{4x + 1} \Rightarrow t^2 = 4x + 1 \Rightarrow \begin{cases} & \mathrm{ 2tdt = 4dx \Rightarrow dx = \dfrac{tdt}{2}} \\ & \mathrm{x = \dfrac{t^2 - 1}{4} }\end{cases}}$

$\mathrm{\Rightarrow \int_{2}^{6}\dfrac{dx}{2x+1+\sqrt{4x+1}} = \int_{2}^{6}\dfrac{tdt}{(t + 1)^2}}$

Đến đây đơn giản rồi